Re-defining Anglo-Argentine literature: from travel writing to travelling identities - Ferradas, Claudia Mónica (2011)
This study proposes a definition of Anglo-Argentine literature, a literary corpus that has not been explicitly defined, and provides a reading list of Anglo-Argentine works on the basis of that definition.